2011
DOI: 10.1161/circulationaha.110.948570
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Genome-Wide Association Studies in >80 000 Subjects Identifies Multiple Loci for C-Reactive Protein Levels

Abstract: Background C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We aimed to identify genetic variants that are associated with CRP levels. Methods and Results We performed a genome wide association (GWA) analysis of CRP in 66,185 participants from 15 population-based studies. We sought replication for the genome wide significant and suggestive loci in a replication panel comprising 16,540 individuals from ten independent studies. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
486
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 469 publications
(511 citation statements)
references
References 33 publications
20
486
5
Order By: Relevance
“…Although none of these SNPs have been associated with RA in other studies, rs2522056 has been associated with Crohn's disease (42), an increase in acute phase response (43) and fibrinogen levels and, therefore, can be considered a risk factor for cardiovascular disease (44). The TRAF3IP2 gene has been associated with the risk of developing psoriasis (45) and psoriatic arthritis (46); ICOS, with alopecia areata; KIAA1542, with the presence of anti-dsDNA antibody postivity in systemic lupus erythematosus (47), with the function of the intergenic region between KIAA1919 and REV3L being unknown.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 80%
“…Although none of these SNPs have been associated with RA in other studies, rs2522056 has been associated with Crohn's disease (42), an increase in acute phase response (43) and fibrinogen levels and, therefore, can be considered a risk factor for cardiovascular disease (44). The TRAF3IP2 gene has been associated with the risk of developing psoriasis (45) and psoriatic arthritis (46); ICOS, with alopecia areata; KIAA1542, with the presence of anti-dsDNA antibody postivity in systemic lupus erythematosus (47), with the function of the intergenic region between KIAA1919 and REV3L being unknown.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 80%
“…This was not unexpected as there is no evidence that CRP expression is regulated directly by HNF4A. Interestingly, a recent GWAS reported that common alleles near HNF4A were associated with CRP levels in healthy individuals; the small effect seen might be mediated indirectly via the regulation of HNF1A by HNF4A [19]. It is a challenging task to discriminate between patients with HNF1A-MODY and those with HNF4A-MODY by clinical presentation alone [20].…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale collaborative attempts to find actual genes that underlie this genetic variation are underway. In 2011, a meta-analysis of genome-wide association (GWA) studies of CRP in over 80,000 subjects identified several genes implicated in the functioning and inflammation of immune system (CRP,IL6R,NLRP3,IL1F10,IRF1,PPP1R3B,SALL1,PABPC4,ASCL1,RORA,and BCL7B) and the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) to be associated with circulating CRP levels (Dehghan et al, 2011). In a meta-analysis of six GWA studies on fibrinogen in over 22,000 subjects, significant genome-wide hits were found in the FGB, IRF1, PCCB, and NLRP3 genes (Dehghan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%